UNCOVERING DIVERSIFICATION BENEFITS: RETURN SPILLOVERS IN USA ESG AND NON-ESG ORIENTED BANKS: Received: 05th August, 2024 Revised: 29th August 2024, 10th September 2024, 29th September 2024 Accepted: 23rd August, 2024 - Zafar, Madiha; Qarni, Muhammad Owais (PEOPLE: International Journal of Social Sciences, 2024)
The balance sheet is a source of interconnectedness among financial products and affect the overall system of economics. Due to interest of investors in the market’s connectedness, our study identifies the dynamics of spillover and their effects on ESG and non-ESG oriented banks of USA. This study comprises the dataset of 2319 observations for the duration of January 1, 2015, to November 22, 2023. The spillover index of Diebold and Yilmaz (2012) was employed to perform the analysis of ESG and non-ESG-oriented banks in USA. This study revealed a difference of interconnectedness between the ESG and non-ESG-oriented banks, specifically during normal and COVID-19 pandemic periods. ESG-oriented banks are highly interconnected with the momentous spillover among each other, indicating a need to manage risk by cross-market diversification. Contrary, non-ESG-oriented banks exhibited minimum interconnectedness and spillover impact. The benefits of diversification were highlighted in this study between ESG and non-ESG-oriented banks. This study summed up that diversification has significant benefits of risk reduction. Results suggested that banks include both the ESG and non-ESG-oriented investments in their portfolio to mitigate the risk. The adoption of banks-only ESG standards leads to investing in fewer projects and fabricated ESG constraints of portfolio optimization. By this way, investments in ESG constrain and restrict the diversification benefits of the portfolio, which maximizes the risk and fragility.